Identifying Emotional and Behavioral Factors Affecting School Dropout Intentions - Sargsyan, Arman; Holloway, Ethan (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to explore the emotional and behavioral factors shaping school dropout intentions among secondary-school students. This qualitative study employed a semi-structured interview design to capture students’ lived experiences and internal processes related to dropout intention. A total of 26 participants from various regions across Canada were selected through purposive sampling to ensure representation of students who had expressed dropout intention or were considered at risk. Interviews were conducted in person or through secure online platforms, recorded with consent, and transcribed verbatim. Data collection continued until theoretical saturation was reached. NVivo software was used to support systematic coding and theme development through inductive thematic analysis. Trustworthiness was enhanced through peer debriefing, reflexive memoing, and maintaining an audit trail throughout the analytic process. Analysis revealed four overarching categories influencing dropout intention: emotional determinants, behavioral risk patterns, interpersonal and social influences, and motivational–cognitive barriers. Emotional determinants such as stress, anxiety, and low self-esteem significantly contributed to dropout inclination, while behavioral patterns—including absenteeism, academic disengagement, and digital overuse—amplified existing vulnerabilities. Interpersonal and social influences, particularly peer dynamics, teacher support, family conflict, and school climate, demonstrated strong associations with disengagement trajectories. Motivational and cognitive factors, including low academic motivation, poor self-regulation, and limited future orientation, further intensified withdrawal considerations. Collectively, the themes highlighted dropout intention as a multidimensional process shaped by interacting emotional, behavioral, relational, and motivational conditions. Findings demonstrate that dropout intention emerges from the interplay of psychological strain, disengagement behaviors, social contexts, and motivational deficits, emphasizing the need for early identification and holistic support systems. Interventions addressing emotional well-being, relational support, behavioral regulation, and academic motivation may reduce dropout intention among school-aged youth.